DESIGN OF OCCUPATIONAL SAFETY TRAINING FOR SINGLE PARENTS OF WEDORO SIDOARJO SHOE WORKERS - Aulia, Raiza (Universitas Pendidikan Ganesha, 2021)
Work safety for workers is very important to be fulfilled in terms of complete personal protective equipment such as boots, and at least with the use of masks. This is important because the effects that arise when the use of personal protective equipment is not used properly can interfere with health. One of them is the shoe craftsman Wedoro Sidoarjo. This made the researchers make a training plan for single parents of shoe craftsmen in Wedoro Sidoarjo to pay more attention to work safety if not done with the right standards it will affect the children at home. The implementation of this training was made based on the results of interviews with the sole parent of shoe craftsman Wedoro Sidoarjo. This training can be done in groups. Implementation carried out in groups will look like real social life. The number of participants from group training should be no more than 16 people because the number of groups that are too large will result in the ineffectiveness of the training (Kelly, 1982; Michelson, et al. 1985; Ramdhani, 2015). This training was conducted at the Nur Rahma Sidoarjo Foundation by 16 single parents. Participants will be given knowledge about good parenting styles for children, knowing the principles of child development, and occupational health and safety. Each material provided will include games, roleplay, and watching movies.